Reflexive Thematic Analysis for Applied Qualitative Health Research - Campbell, Karen; Orr, Elizabeth; Durepos, Pamela; Nguyen, Linda; Li, Lin; Whitmore, Carly; Gehrke, Paige; Graham, Leslie; Jack, Susan (Qualitative report, 2021)
Thematic analysis is a widely cited method for analyzing qualitative data. As a team of graduate students, we sought to explore methods of data analysis that were grounded in qualitative philosophies and aligned with our orientation as applied health researchers. We identified reflexive thematic analysis, developed by Braun and Clarke, as an interpretive method firmly situated within a qualitative paradigm that would also have broad applicability within a range of qualitative health research designs. In this approach to analysis, the subjectivity of the researcher is recognized and viewed not as problematic but instead valued as integral to the analysis process. We therefore elected to explore reflexive thematic analysis, advance and apply our analytic skills in applied qualitative health research, and provide direction and technique for researchers interested in this method of analysis. In this paper, we describe how a multidisciplinary graduate student group of applied health researchers utilized Braun and Clarke’s approach to reflexive thematic analysis. Specifically, we explore and describe our team’s process of data analysis used to analyze focus group data from a study exploring postnatal care referral behavior by traditional birth attendants in Nigeria. This paper illustrates our experience in applying the six phases of reflexive thematic analysis as described by Braun and Clarke: (1) familiarizing oneself with the data, (2) generating codes, (3) constructing themes, (4) reviewing potential themes, (5) defining and naming themes, and (6) producing the report. We highlight our experiences through each phase, outline strategies to support analytic quality, and share practical activities to guide the use of reflexive thematic analysis within an applied health research context and when working within research teams.